2015
DOI: 10.1631/jzus.b1500055
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological comparison of taxa comprising the Sporothrix schenckii complex

Abstract: Based on recent molecular data, it has been suggested that Sporothrix globosa is the main causal agent of sporotrichosis in China. The objective of this study was to compare the morphology, growth characteristics, patterns of carbon source usage, and susceptibility to antifungal agents among Sporothrix strains. A total of 15 clinical strains confirmed to be S. globosa, from three different regions of China, and 11 ex-type strains from the CBS-KNAW biodiversity center were obtained. The elongated conidia of S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…is usually isolated in 4-6 days, for samples collected from skin lesions, and in 10-19 days, for extracutaneous lesions; time can also vary depending on the species of Sporothrix. 73 , 76 , 78 , 79 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…is usually isolated in 4-6 days, for samples collected from skin lesions, and in 10-19 days, for extracutaneous lesions; time can also vary depending on the species of Sporothrix. 73 , 76 , 78 , 79 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Assimilation of sugars such as glucose, raffinose, ribitol, and sucrose are some of the carbon compounds used in physiological tests; the Sporothrix isolates show different pattern of assimilation. 79 …”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…7 , 8 Many molecular studies have demonstrated that S. globosa is the most prevalent etiologic agent of sporotrichosis in China. 8 , 9 , 10 , 11 , 12 Several retrospective studies of clinical S. schenckii isolates from China using random amplified polymorphic DNA analysis 13 , 14 and restriction fragment length polymorphism analysis 15 have shown a correlation among the genotypes, clinical forms, and geographic origins of isolates, although S. schenckii was not differentiated from S. globosa or other Sporothrix species.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of scientific literature produced in recent years highlighted important phenotypic and genetic differences not only among the different clades with high or reduced pathogenic potential but also among closely related taxa belonging to a specific group (Fernandes et al 2013; Romeo and Criseo 2013; Sasaki et al 2014; Zhao et al 2015). In fact the degree of virulence observed among members of the pathogenic clade can be defined as S. brasiliensis > S. schenckii > S. luriei > S. globosa (Arrillaga-Moncrieff et al 2009; Fernández-Silva et al 2012).…”
Section: Discussionmentioning
confidence: 99%